Literary translation as a forging pivot of aesthetic movements: the unique case of Vltra. - Enríquez-Aranda, Mercedes (My University, 2023)
The literary and cultural periodical Vltra is analyzed during the period 1921-1922 as being “the last commitment assumed by the signatories of the manifesto that under this title appeared in all the Madrid newspapers in the autumn of 1918” and which laid the foundations of Ultraism as a poetic movement that promoted a radical renewal of spirit and technique. Through the study of its translations, we can analyze the foreign sources that served as inspiration for the movement and their treatment in translation, with the consequent influence on the Spanish literary panorama of the time.
Keywords: Traducciones; Literatura - Publicaciones periódicas - España - S. XX; Vltra (Madrid) - Historia y crítica; Literary translation; Translation history; Ultraism; Canon; Retranslation; Traducción literaria; Historia de la traducción; Ultraísmo; Retraducción